Anti-ulcer effects of cumin (Cuminum cyminum L.), thyme (Thymus vulgaris L.), and caraway (Carum carvi L.) essential oils on peptic ulcer and ulcerative colitis models in rats - Nehad Naem Hamed Shosha; Nouran M. Fahmy; Abdel Nasser B. Singab; Radwa Wahid Mohamed (Shahrekord University of Medical Sciences, 2022)
Introduction: Essential oils are considered a potential alternative to synthetic drugs in the management of diseases such as peptic ulcer (PU) and ulcerative colitis (UC). This study is concerned with comparing the therapeutic effects of Cuminum cyminum L, Carum carvi L, and Thymus vulgaris L. essential oils on PU and UC models induced by ethanol. Methods: Rats were divided into 10 groups; control groups were treated with saline and experimental groups with 500 mg/kg body weight of C. cyminum, C. carvi, or T. vulgaris essential oil. Curative effects were determined by measuring tissue oxidative markers, such as reduced glutathione (GSH), malondialdehyde (MDA), and myeloperoxidase (MPO), as well as the inflammatory marker prostaglandin E2 (PGE2), stomach pepsin (PEP), and colon alkaline phosphatase (ALP). Biochemical and histological examinations were done on stomach and colon tissues. Results: The current study proved the anti-ulcer effects of C. cyminum, C. carvi, and T. vulgaris essential oils. They improved the oxidative and inflammatory markers in both stomach and colon tissues and modulated stomach PEP and colon ALP activities. T. vulgaris essential oil modulated GSH and MDA levels resulting in a significant elevation in GSH levels by 120.43% and 99.46% and a significant reduction in MDA levels by 20.05% and 24.1% in PU and UC models, respectively. C. carvi essential oil was the most effective in restoring PGE2 by 71.51% compared to UC group. Results were confirmed by the morphological and histopathological changes. Conclusion: C. cyminum, C. carvi, or T. vulgaris essential oils might be used in the management of acute PU and UC.